R E L A T I O N S H I P M A R K E T I N G I N T H E R E T A I L S E C T O R - Sagat, Gerhard Michael (My University, 2011)
South African companies operating in the retail sector are increasingly embarking on relationship marketing strategies. However, several companies both locally and abroad have reported failures in the implementation of these strategies, citing a host of various reasons. An investigation into the factors contributing towards successful relationship marketing strategies and an evaluation of the performance of South African companies engaged in these practices was undertaken. The methodology employed consisted of two distinct stages. First, a comprehensive literature review was conducted to identify the factors that contribute towards successful relationship marketing. Thereafter, a survey by way of a questionnaire was conducted to identify additional factors, as well as evaluate the performance of South African companies engaged in this practice. The sample of 25 respondents was selected using a non-probability sampling technique and consisting of three distinct sub-segments i.e. practitioners, academics and consultants in the field of relationship marketing. The results from the survey were content analysed. The study revealed that South African companies engaged in relationship marketing were, in the most, effectively managing this discipline. However, room for further improvement within in these organisations was evident, as certain known factors to influence relationship marketing success were not being properly managed. What‟s more, South African companies engaged in this practice appeared to have a self-biased understanding and approach to relationship marketing. To help organisations improve the effectiveness and success of their relationship marketing initiatives, a process model incorporating the findings from the literature review and the research was developed.
MBA thesis - WBS
Keywords: Relationship marketing; Retail sector